Analysis on the Impact of the MBKM Program on Improving the Competence of Teacher Training Students: A Study of Student Perceptions of the Teacher Training and Education Faculty - Lathifah, Zahra Khusnul; Rusli, Radif Khotamir; Prasetyo, Teguh; Febrianisya, Mega; Kholik, Abdul; Suherman, Irman (Jurnal Paedagogy, 2022)
This study aims to analyze more deeply the impact of the MBKM program carried out by the Ministry of Education and Culture on improving student-teacher competence, and, at the same time, see the extent to which students understand the results and impact of students’ potential development from the students’ point of view. The type of research used is quantitative research with survey methods. Data collection techniques using a google form based questionnaire. The sample in this study were students of the Faculty of Teacher Training and Education (FKIP) of Djuanda University, which consisted of 3 study programs with a total of 504 students. The data is analyzed through several stages: organize, sort, group, code the data and categorize. The research findings showed that the MBKM program positively impacted student competency development, as evidenced by the results of the questionnaire analysis of student perceptions of MBKM by 80.3%. MPI study program students stated that there was an increase in competence and skills as a provision for work by 7%m, 47% said it was good, 40% said it was pretty good, and 7% said it was not good. PGSD study program students stated that 6% were excellent, 38% were good, and 52% were quite good. Meanwhile, the PBA study program students stated they were very good at 13%, 45% were good, 37% were quite good, and 5% were not good.